Tìm x biết (2x+1)10=(2x+1)11
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(2x-1\right)^{10}=\left(2x-1\right)^{11}\)
\(\Leftrightarrow\orbr{\begin{cases}2x-1=0\\2x-1=1\end{cases}\Leftrightarrow\orbr{\begin{cases}2x=1\\2x=2\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{1}{2}\\x=1\end{cases}}}\)
(2x-1)10 = (2x-1)11
(2x-1)10-(2x-1)11=0
(2x-1)10.[1-(2x-1)1 ]=0
\(\Rightarrow\orbr{\begin{cases}\left(2x-1\right)^{10}=0\\1-\left(2x-1\right)^1=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x-1=0\Rightarrow2x=1\Rightarrow x=\frac{1}{2}\\2x-1=1\Rightarrow2x=2\Rightarrow x=2:2=1\end{cases}}\)
Vậy \(x\in\left\{\frac{1}{2};1\right\}\)
\(\left(2x-1\right)^{10}=\left(2x-1\right)^{11}\)
\(\Leftrightarrow\orbr{\begin{cases}2x-1=1\\2x-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x=\frac{1}{2}\end{cases}}\)
Vậy ...........
\(\Rightarrow\left(2x-1\right)^{11}-\left(2x-1\right)^{10}=0\)
\(\Rightarrow\left(2x-1\right)^{10}.\left[\left(2x-1\right)-1\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(2x-1\right)^{10}=0\\\left(2x-1\right)-1=0\end{cases}\Rightarrow\orbr{\begin{cases}2x-1=0\\2x-1=1\end{cases}}}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=1\end{cases}}\)
Vậy \(x\in\left\{\frac{1}{2};1\right\}\)
1) \(\left|x\right|< 10\)
\(\Leftrightarrow-10< x< 10\)
2) \(\left|x\right|>11\)
\(\Leftrightarrow\left[{}\begin{matrix}x< -11\\x>11\end{matrix}\right.\)
3) \(\left|x\right|\ge2x\left(\forall x\ge0\right)\)
\(\)\(\Leftrightarrow\left[{}\begin{matrix}x\le-2x\\x\ge2x\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}3x\le0\\x\le0\end{matrix}\right.\)
\(\Leftrightarrow x=0\) \(\left(thỏa.đk:x\ge0\right)\)
4) \(\left|x\right|\le-3x\left(\forall x\le0\right)\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ge-\left(-3x\right)\\x\le-3x\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}2x\le0\\4x\le0\end{matrix}\right.\)
\(\Leftrightarrow x\le0\) \(\left(thỏa.đk\right)\)
a)(x+2).(x+3)-(x-2).(x+5)=10
( x^2 +3x+2x+6)-(x^2 +5x-2x-10)=10
x^2 +3x+2x+6-x^2 -5x+2x+10-10=0
2x+6=0
2x=-6
x=-3
Xét cấp số cộng 1, 6, 11, ..., 96.
Ta có: 96 = 1 + 5(n − 1) ⇒ n = 20
Suy ra
Và 2x.20 + 970 = 1010
Từ đó x = 1
\(\Leftrightarrow\)4.(x2+2x+1)+4x+4x2+1-8(x2+10x-x-10)=11
\(\Leftrightarrow\)4x2+8x+4+4x+4x2+1-8x2-80x+8x+80=11
\(\Leftrightarrow\)-60x=-74
\(\Leftrightarrow\)x=\(\frac{37}{30}\)
a) 2x.(1 + 23) = 144
2x . 9 = 144
2x = 16
=> x = 4
b) (2x - 1)10 = (2x - 1)100
(2x - 1)100 - (2x - 1)10 = 0
(2x - 1)10.[ (2x - 1)90 - 1] = 0
=> (2x - 1)10 = 0 hoặc (2x - 1)90 - 1 = 0
=> 2x = 1 hoặc (2x - 1)90 = 1
=> x = \(\frac{1}{2}\) hoặc \(2x-1=\orbr{\begin{cases}1\\-1\end{cases}}\)
=> \(2x=\orbr{\begin{cases}2\\0\end{cases}}\)
=> x = {\(\frac{1}{2};1;0\)}
cảm ơn mn